A new approach for solving multi-objective transportation problems. Issue 3 (3rd July 2017) - Nomani, Mohammad Asim; Ali, Irfan; Ahmed, A.
Abstract: In this paper, a weighted approach based on goal programming to obtain compromise solutions is proposed. In the proposed approach, a new weighted model is presented to obtain varying solutions according to the priorities of the decision-maker. Using this model, consistent results may be generated according to the expectation of the decision-maker that the goal with the higher priority may have a higher level of satisfaction. We have considered a multi-objective transportation problem and solved it using the proposed approach. Comparison has been made with different existing approaches. Different solution approaches for multi-objective transportation problems are also discussed.